STABILIZATION OF SUBGRADE SOILS USING CEMENT AND LIME: A CASE STUDY OF KALA SHAH KAKU, LAHORE, PAKISTAN (Pakistan Journal of Science, 2022)
The purpose of this study has to stabilize subsoil using soil improvement techniques to reduce the cost of construction. For this purpose, disturb samples from Kala Shah Kaku (KSK) were tested to evaluate the effect of different additives on strength of soil. Index properties of soil such as grain size analysis, Atterberg’s limits and specific gravity were also determined for selected soilsamples. Further two different additives i.e. Lime and Ordinary Portland cement (OPC), were chosen for treatment of soil obtained from KSK area. Samples were remolded by addition of additives in varying percentages up to 2-8% cement and 4-15% lime by dry weight of the soil. All the remolded samples were compacted at Optimum Moisture Content (OMC) and Maximum Dry Density (MDD) as per Modified Procter Test and were then subjected to Unconfined Compression strength (UCS) andCalifornia Bearing ratio (CBR) tests. The effect of modifications in engineering properties was evaluated by treated soil samples with aging. Unconfined compressive strength (UCS) was determined in different time intervals i.e. on the same day (immediately after remolding), after 7 days, 14days and 28days.The samples for soaked CBR value were tested after 96 hours. From the study, it was concluded that the application of cement & lime showed tremendous improvement in UCS and CBR value with increase in cement or lime contents. Further, it was found that addition of cement showed better results at an optimum dosage of 4 to 6 percent than optimum percentage for lime i.e. 8%
Keywords: Ground Improvement; Binders; IndexProperties; California Bearing Ratio(CBR); Unconfined Compressive Strength(UCS)